Extracellular vesicles from recombinant cell factories improve the activity and efficacy of enzymes defective in lysosomal storage disorders. Issue 4 (12th March 2021) - Seras‐Franzoso, Joaquin; Díaz‐Riascos, Zamira V.; Corchero, José Luis; González, Patricia; García‐Aranda, Natalia; Mandaña, Mònica; Riera, Roger; Boullosa, Ana; Mancilla, Sandra; Grayston, Alba; Moltó‐Abad, Marc; Garcia‐Fruitós, Elena; et al.
Abstract: In the present study the use of extracellular vesicles (EVs) as vehicles for therapeutic enzymes in lysosomal storage disorders was explored. EVs were isolated from mammalian cells overexpressing alpha‐galactosidase A (GLA) or N‐sulfoglucosamine sulfohydrolase (SGSH) enzymes, defective in Fabry and Sanfilippo A diseases, respectively. Direct purification of EVs from cell supernatants was found to be a simple and efficient method to obtain highly active GLA and SGSH proteins, even after EV lyophilization. Likewise, EVs carrying GLA (EV‐GLA) were rapidly uptaken and reached the lysosomes in cellular models of Fabry disease, restoring lysosomal functionality much more efficiently than the recombinant enzyme in clinical use. In vivo, EVs were well tolerated and distributed among all main organs, including the brain. DiR‐labelled EVs were localized in brain parenchyma 1 h after intra‐arterial (internal carotid artery) or intravenous (tail vein) administrations. Moreover, a single intravenous administration of EV‐GLA was able to reduce globotriaosylceramide (Gb3) substrate levels in clinically relevant tissues, such kidneys and brain. Overall, our results demonstrate that EVs from cells overexpressing lysosomal enzymes act as natural protein delivery systems, improving the activity and the efficacy of the recombinant proteins and facilitating their access to organs neglected by conventional enzyme replacement therapies.